ANALYSIS OF THE DYNAMICS OF THE NORMS OF RUSSIAN WRITTEN SPEECH - Shadieva, Dilrabo (Журнал иностранных языков и лингвистики, 2021)
A linguistic norm (literary norm) is the rules for the use of speech means in a certain period of the development of the literary language, i.e. rules of pronunciation, word use, use of traditionally established grammatical, stylistic and other linguistic means adopted in social and linguistic practice. This is a uniform, exemplary, generally recognized use of language elements (words, phrases, sentences)